A holistic tool for improving technology transfer offices' performance. (4th November 2022) - Granieri, Massimiliano; Frederick, Peter
Public-to-private technology transfer, featuring translational efforts from academia to market, does not achieve homogeneous results across the board. European universities and public research organisations (PROs) prove less performing than colleagues from the USA and this lag has been a major policy issue for European institutions in the last two decades, since R&D investments do not yield appropriate returns in terms of intellectual property, licenses and spin-out companies. Barriers to successful technology transfer are relevant and technology transfer offices (TTOs) as intermediaries in the technology market are underperforming. While studies have been conducted in technology management literature to identify barriers, so far there seems to be a lack of a holistic tool that help measure and improve TTO's performance. In an effort to provide such tool, we use the CCODE ® methodology and adapt it to TTOs. Based on an extensive literature review, we identify five factors that are generally considered determinants of the performance and develop what could be the basis for a diagnostic tool able to help single TTOs and their PROs identifying areas where changes could be made to improve their performance.